Corporate taxation and the location choice of foreign direct investment in EU countries - Ronald B. Davies; Iulia Siedschlag; Zuzanna Studnicka (The Economic and Social Research Institute (ESRI), 2018)
This paper examines the impact of corporate taxation and other factors on the attractiveness of EU countries to foreign direct investment. In comparison to previous analyses on the location choice of multinational activity in the EU, we use an improved empirical methodology to account for more flexible substitution patterns among alternative locations by considering groups of countries with similar characteristics as location options. In addition, we account for the heterogeneity of investors' behaviour by considering intra-EU investments and investments from outside the EU. Furthermore, we identify and quantify similarities and differences with respect to the effects of corporate taxation and the effects of other factors on the location choice of foreign affiliates in manufacturing and services
Keywords: C25; D22; F23; H25; 330; Multinational firms; location choice; corporate tax policy